(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
Shelf-life of potassium sorbate (2%) and gamma irradiation (2kGy) treated Hilsa shad (Tenualosa ilisha) were determined after storing at 0oC and 4oC for a period of upto 35 days. Organoleptic evaluation showed that control, potassium sorbate treated and irradiated samples remained acceptable upto 21, 28 and 35 days of storage periods respectively at 00 C. Whereas, the same samples remained acceptable upto 7, 14 and 21 days of storage respectively at 40 C. Tyrosine and pH of fish flesh increased with the increasing of storage periods in all samples but, this increasing trend was somewhat lower in irradiated sample compare to other samples. Microbial assessment showed the best results in case of irradiated sample and remained within the acceptable limit. Jahangirnagar University J. Biol. Sci. 6(2): 67-73, 2017 (December)